Outcomes of Hepatic Resections for Synchronous Colorectal Liver Metastases in a Low-volume Setting - Jearwattanakanok, Kijja (The Thai Journal of Surgery, 2013)
Objective: To assess outcomes of hepatic resections for synchronous colorectal liver metastases in a lowvolume setting. Materials and Methods: Medical records of patients undergoing hepatic resections for synchronous colorectal liver metastases from October 2003 to September 2012 were reviewed. Progression-free survival was estimated with the Kaplan-Meier method. Risk factors of disease progression were identified and tested using the Cox proportional hazards regression models. Results: There were 21 patients who underwent hepatic resection for synchronous colorectal metastasis. There was no hospital death.Operative morbidity was 38% (8 of 21 patients). Progression was observed in 9 patients, of whom 5 died. Median progression-free survival was 30 months. Increased Fong’s clinical risk score (HR: 4.03;95% CI: 1.35 to 11.97), preoperative carcinoembryonic antigen > 200 ng/mL (HR: 5.43;95% CI: 1.21 to 24.40), and positive resection margin (HR: 9.70; 95% CI: 2.12 to 44.37) were associated with higher risk of disease progression. Conclusion: Hepatic resection for colorectal liver metastases can be performed in low-volume settings with good outcomes. Selection of low-risk patients is advised.